Design of Triaxial Production Device - Kascak, Jakub; Teliskova, Monika; Torok, Jozef; Kocisko, Marek; Pollak, Martin (Manufacturing Technology Journal, 2018)
Like most new technologies, 3D printing has long been a domain of narrowly specialized fields. However, the potential of this technology is enormous and thus it has been gradually finding its application in ever-newer sectors. This paper focuses on the structure and overall implementation of a triaxle manufacturing device inspired by an existing 3D printer design based on the modular RepRap concept. The result is a functional triaxle manufacturing device capable of performing 3D printing and laser cutting or laser engraving.
Keywords: Manufacturing equipment; Laser engraving; FFF technology; ZMORPH 2.0 SX